A produção de biojoias no Norte do Brasil : como as sementes são ressignificadas em redes de sustentabilidade - Schierholt, Anelise Fabiana Paiva (Universidade do Vale do Rio dos Sinos, 2019)
This thesis aims to discuss the associative arrangements established by the artisans of bio jewelry, eco jewelry, and dolls in the collective work of the artisans from the Açaí Cooperative at Porto Velho, (Roraima state in Brazil) trying to recognize their combinations in national and locals sustainability networks. The artifacts production took local and regional seeds and fibers from the Amazon biome, as also agroecological cotton streams, stripes, and fabrics from Justa Trama. The combinations operated by the Cooperative disclose perceptions of environmental sustainability and identitarian commitments. These commitments express the organizing principles for realizing the sustainability networks actions. Furthermore, bio jewelry and eco jewelry productions generate diversity representations and reinforce the built of an Amazon identity. Meantime, dolls production implies in rethinking the collective work. This research used a qualitative research methodology with an ethnographic approach. The direct observation of the researched phenomena resulted in the elaboration of a field journal, the realization of semistructured interviews, as well as the production of videos and photographies about the context in which the subjects are.
Keywords: Biojoias; Cooperativa Açaí; Justa Trama; Redes de sustentabilidade; Bio jewelry; Açaí Cooperative; Justa Trama; Sustainability networks; ACCNPQ::Ciências Humanas::Sociologia